Proceedings of the Tribunal of Arbitration [electronic resource] : convened at Paris under the treaty between the United States of America and Great Britain, concluded at Washington, February 29, 1892, for the determination of questions between the two governments concerning the jurisdictional rights of the United States in the waters of Bering Sea. - Bering Sea Tribunal of Arbitration.; United States. (Washington : G.P.O., 1892)
Tables. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14470-14486. At head of title: Fur seal arbitration. "Volume VIX." Includes indexes. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44